Anemia in women of reproductive age, household food insecurity, food consumption and household food production practices in southwestern Bangladesh. - Gurung, Sabi. (Tufts University. Tisch Library., 2017)
This poster shows data from a longitudinal observation study taking place in Bangladesh, examining nutritional status. It was presented by Sabi Gurung at the 5the Annual Scientific Symposium in Nepal.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy